Analisis Pengaruh Tingkat Pendapatan Usahatani Padi Warga Kecamatan Pagak Dalam Menciptakan Swasembada Kampung - Abdullah Syakur Novianto,; Arief Yuswanto Nugroho, (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2021)
This study aims to determine whether the Village Unit Cooperative (KUD) pagak distict able to prosper farmers in Indonesia. The data used to examine the purposes of this study is the IFLS (Indonesian Family Life Survey) data by applying multiple linear regression analysis. The result of the analysis found that there is no strong evidence that farmers who use KUD Pagak loan funds have better rates of income from farmers who do not use loans from KUD Pagak. This indicates that farmers 'membership in the KUD Pagak has not been clearly visible as to the improvement of farmers' welfare. Other results of the analysis show that entrepreneurial spirit negatively affects farmers' income from farming. This negative relationship shows that, if a person has a high entrepreneurial spirit, then that person will be more inclined not to enter the field of agricultural business. Education has no significant effect on farming activities, but the experience and physical labor of men who have a positive effect on farm income.